Teaching Research : Evaluation and Assessment Strategies for Undergraduate Research Experiences (TREASURE) : Final Report. - Howitt, Susan; Wilson, Anna; Higgins, Denise (Office for Learning and Teaching, 2014)
Final report from a project that aimed to improve the effectiveness of programs that use undergraduate research experiences to foster generic and research skills. Such experiences are increasingly being included as assessed components in coursework degrees. Studies have shown that both students and academics exhibit a wide range of perceptions of the nature and value of these experiences, and it appears that prior expectations and perceptions may limit potential and actual learning outcomes. This proposal promoted the use of reflective practice within research experiences to develop deeper understandings of research and to provide evidence of changes in critical thinking on which to base assessment. Workshops with staff resulted in the development of frameworks for reflective practice, with specific disciplinary components to help students better understand both of the nature of research and the way in which research experiences foster generic skills.